Intracranial extension of orbital inflammatory pseudotumor: a case report and literature review. Issue 1 (December 2016) - Tedeschi, Enrico; Ugga, Lorenzo; Caranci, Ferdinando; Califano, Francesca; Cocozza, Sirio; Lus, Giacomo; Brunetti, Arturo
Abstract Background Orbital inflammatory pseudotumor is a rare inflammatory condition of unknown cause that may extend intracranially, usually as a dural-based infiltrate. Here we report the first case of orbital pseudotumor presenting with intra-axial Magnetic Resonance Imaging (MRI) changes. Case presentation A 57-year-old white female, with a 3-month history of headache and right palpebral edema, presented with marked right temporal lobe edema with ominous MRI appearance, and ipsilateral alterations of orbital and periorbital structures. Following steroid therapy, both intracranial and orbital involvement dramatically improved. Conclusion Orbital inflammatory pseudotumor with chronic inflammation may infrequently present with intracranial involvement, mimicking more aggressive diseases, even showing intra-axial enhancement after i.v. contrast administration in brain MRI. Awareness of this possibility may help neurologists to choose the appropriate therapeutic approach.